Round Table: Re-writing history in the era of commemoration - Catherine DELMAS (E-REA)
As part of the round table organized during the conference, this paper is a presentation of the research conducted by the CEMRA at Stendhal University-Grenoble3 on memory, history and fiction, followed by a reflection on the issue of commemoration.